Enhancing the water-resistance of MOF-199 film through incorporation of microporous organic networks for solid-phase microextraction of BTEX in aqueous environments with improved efficiency - Yang, Xiao-Qin; Yu, Li-Qing; Li, Lan-Fen; Lv, Yun-Kai (Analytica chimica acta, 2024)
The practical application of moisture sensitive metal organic frameworks (MOFs) in extraction technology faces challenges related to competitive adsorption and water stability. The target analytes cannot be effectively extracted under humid conditions due to the competitive moisture adsorption and/or framework structure collapse of MOFs. In this study, the microporous organic networks (MONs) were synthesized through Sonogashira coupling reaction to use for hydrophobic modification on the surface of MOF-199. The MOF-199@MON as coating was deposited on stainless steel wires for solid-phase microextraction (SPME) of benzene series (BTEX) in aqueous environments. Under the optimal extraction conditions, the MOF-199@MON coated fiber for SPME coupled with GC-MS for the determination of BTEX gave the linear range of 0.5–500 μg L−1, the limit of detections (LODs, S/N = 3) of 0.01–0.04 μg L−1, the limit of quantifications (LOQs, S/N = 10) of 0.04–0.12 μg L−1, the enhancement factors of 3567–4878, and the intra-day, inter-day and fiber-to-fiber precisions (relative standard deviations, RSDs) of 1.0–9.8, 1.9–7.9 and 4.5–9.5 %, respectively. The developed method was successfully applied to the analysis of BTEX in water samples with the recoveries of 71.0 %–113 %. This work reveals the home-made SPME fibers have a long service life (the extraction efficiency of fiber decreased by only 7.26 %−13.14 % after 100 cycles). The potential of MON functionalized MOFs as effective adsorbents for the SPME of pollutants in the water environment. The surface of MOF-199 was modified with microporous organic networks (MONs) through Sonogashira coupling reaction, and then the MOF-199@MON used as solid-phase microextraction coating for enriching benzene series in aqueous environments. [Display omitted] •The surface of MOF-199 was modified with microporous organic networks (MONs) through Sonogashira coupling reaction to improve its water stability.•The MOF-199@MON as solid-phase microextraction coating was used to enrich BTEX in aqueous environments.•The self-made MOF-199@MON fibers have good extraction and a long service life.•Incorporation of MON largely improved the water-resistance of MOF-199@MON coatings, also enhanced extraction efficiency to BTEX.